Interactions of Landscape and Wildfire: Landscape Management Implications - Prof. C. R. Mohanty, Prof. P. K. Mohapatra, Prof. S. K. Behera, Dr. Bandana Khuntia (International Journal of Modern Agriculture, 2020)
Around half a million hectares of land in Southern Europe are consumed every year by wildfires which cause great environmental and socio-economic effects. Changes in climate and land use have increased the risk and danger of fire in recent decades. This paper analyzes scientific knowledge available on the relationship between the Mediterranean ecosystem and wildfires, with a focus on their implementation to identify landscape management recommendations and strategies that may be implemented to encourage ecosystems that are less fire-dangerous. The key results are that socio-economic factors have positively supported improvements in land management leading to an increase in fire risk in the past decade, major wildfires become more regularly occurring and the increase in fires occurrence promotes homogenous ecosystems protected by fire-prone shrub lands. There are also major gaps in knowledge about the challenges to address these issues and the policy and landscape management response that need to be adopted.